2018
DOI: 10.31871/ijntr.4.9.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-C and Ozone on the Bioactive Compounds and Antioxidant Capacity of Minimally Processed Rocket (Eruca Sativa Mill.)

Abstract: In this study, treatments with UV-C radiation (10, 20 and 30 kJ/m2) and gaseous ozone (1, 5 and 10 mg/L) were applied to minimally processed rocket (Eruca sativa) leaves to investigate their effects on the bioactive compounds and antioxidant capacityduring12 days of storage at 5 ºC.As control, water washing was used. Ascorbic acid content, phenolic compounds, antioxidant capacity and chlorophyll a and b, total chlorophyll and total carotenoids content throughout shelf-life were studied. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…To minimize microbial hazards of minimally processed fruit and vegetable besides washing raw material in water with the addition of disinfectant, also treatment with UV and ozone are practiced. It was found that treatment with UV-C ultraviolet radiation (100-280 nm; 10, 20, and 30 kJ/m 2 ) and gaseous ozone (1, 5, and 10 mg/L) had no adverse effect on vitamin C in minimally processed rocket leaves during 12 days of storage at 5 °C [ 137 ].…”
Section: Innovative Non-thermal Technologies In Fruit and Vegetabmentioning
confidence: 99%
“…To minimize microbial hazards of minimally processed fruit and vegetable besides washing raw material in water with the addition of disinfectant, also treatment with UV and ozone are practiced. It was found that treatment with UV-C ultraviolet radiation (100-280 nm; 10, 20, and 30 kJ/m 2 ) and gaseous ozone (1, 5, and 10 mg/L) had no adverse effect on vitamin C in minimally processed rocket leaves during 12 days of storage at 5 °C [ 137 ].…”
Section: Innovative Non-thermal Technologies In Fruit and Vegetabmentioning
confidence: 99%
“…The researchers demonstrated that, by correctly defining dose of ozone during the fumigation of red-veined sorrel plants applied at a concentration of 1 ppm, it is possible to increase the contents of polyphenols in raw material. Gutiérrez et al [25] reported that ozone treatment applied for 10 min to Rocket plant (Eruca sativa Mill.) at a rate of 1 and 10 ppm results in increased contents of polyphenols in the material.…”
Section: Chemical Composition Of Hs-spmementioning
confidence: 99%
“…These biochemical changes also stimulate the enzymatic antioxidant activity that detoxify the cell of ROS to less harmful species or water (Huang et al 2019). Indeed, it is well documented that UV-C affects stress responses; activates metabolic pathways, defense mechanisms, and the susceptibility of the hosts against rotting microorganisms; counteract the damage postharvest; and extend the shelf life of fresh fruit cold-storage (Reque et al 2014;Gutiérrez et al 2018). Fig.…”
Section: Discussionmentioning
confidence: 99%